Contact analysis for different viscoelastic contact force models - Alves, Janete (2013)
t is well known that the nature of the constitutive contact force law utilized to describe contact-impact events in the context of multibody dynamics plays a key role in predicting the response of mechanical systems and simulation of the engineering applications. Thus, the main aim of this work is to present a comparative study of different continuous contact models regarding the multibody system dynamics formulation. The main issues of several conservative, dissipative and frictionless force models will be presented, as well as the main differences and similarities between them for distinct input data, such as different coefficient of restitution values. The results were performed regarding the well- known bouncing ball problem, a simple system to compare the different contact force models presented along this paper. In general, the outcomes from the dynamic analyses of the different models indicate that the prediction of the dynamic behavior of contacting bodies strongly depends on the selection of the contact force model.